The performance of the second board index in relation with the composite index / Kasmah A. Karim - A. Karim, Kasmah (1995)
This study looks into the performance measurements of the Second Board Index in relation with the Composite Index proxied as the market portfolio. This study also looks into the relationship between the Second Board Index and the Composite Index and to test whether there is any correlation exists between the two Indices. To measure the Indices' performances, the Sharpe, Treynor and Jensen Indices are used. These Indices were basically developed by their respective authors to measure the performance of mutual funds. Still, they can be used to measure the performance of individual stocks, as Wendy Foo, the Senior Lecturer of the School of Accountancy and Business of Nanyang Technological Institute pointed out in her article entitled " Performance of the Bank Stocks in the Singapore Market " published in the Security Industry Review, 1989. The Pearson Product Moment Correlation method is used to test the existence of correlation between the Second Board Index and the Composite Index. To test the significance of the correlation, the t-test is carried out using the 5% level of significance. Weekly data from February 1991 to December 1994 are gathered for this study.